2018
DOI: 10.1017/jfm.2018.282
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of a sloping solid surface by turbulent compositional convection

Abstract: We examine the dissolution of a sloping solid surface driven by turbulent compositional convection. The scaling analysis presented by Kerr & McConnochie (J. Fluid Mech., vol. 765, 2015, pp. 211–228) for the dissolution of a vertical wall is extended to the case of a sloping wall. The model has no free parameters and no dependence on height. It predicts that while the interfacial temperature and interfacial composition are independent of the slope, the dissolution velocity is proportional to $\cos ^{2/3}\un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 26 publications
1
31
1
Order By: Relevance
“…Here we assume a flat (nonsloping) ice shelf, for which melting does not generate a buoyant plume. Recent LES (29) demonstrated that flat ice shelf results can also be extended to basal slope angles of up to 5 • , a result that is consistent with plume theory (50). Over large scales, basal slopes in ice shelf drafts are extremely small, with smaller angles near the front and somewhat steeper angles near the grounding line (7).…”
Section: Methodssupporting
confidence: 57%
“…Here we assume a flat (nonsloping) ice shelf, for which melting does not generate a buoyant plume. Recent LES (29) demonstrated that flat ice shelf results can also be extended to basal slope angles of up to 5 • , a result that is consistent with plume theory (50). Over large scales, basal slopes in ice shelf drafts are extremely small, with smaller angles near the front and somewhat steeper angles near the grounding line (7).…”
Section: Methodssupporting
confidence: 57%
“…Figure 14 illustrates the development of a regular pattern of convective rolls which flow along the surface of the body, characterised by a much thicker boundary-layer region compared to the laminar region shown in figure 14. Experiments of turbulent composition free convection of ice melting into ambient salty water (Kerr & McConnochie 2015; McConnochie & Kerr 2018) indicate that the rate of heat or solutal transfer in this regime becomes independent of the distance moved downstream of the body, but still depends on the local slope. It is anticipated that an evolution equation analogous to the kind we have developed (2.16 a , b ) could be derived to couple a transfer law applicable to turbulent free convection to the shape evolution and analysed to derive shape evolutions in this case.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…McConnochie and Kerr, 2018;Mondal et al, 2019). However, we emphasize that further investigation is needed beyond the small number of simulations presented here to validate our results.…”
Section: Insights Into Melt Rate Sensitivity To Ocean Conditionsmentioning
confidence: 63%